ABO blood group antigen mismatch has an impact on outcome after allogeneic peripheral blood stem cell transplantation. Issue 11 (3rd October 2016) - Grube, Matthias; Wolff, Daniel; Ahrens, Norbert; Herzberg, Philipp Y.; Herr, Wolfgang; Holler, Ernst
Abstract: ABO blood group antigen incompatibility (ABO mismatch) is not an obstacle to allogeneic stem cell transplantation (allo‐SCT). However, the impact on clinical outcome after allo‐SCT remains controversial. We analyzed 512 patients after allogeneic peripheral blood SCT (allo‐PBSCT) for an association of ABO mismatch with transfusion requirements, myeloid and platelet engraftment, the incidence of GvHD, relapse, transplant‐related mortality (TRM), and overall survival (OS). A total of 260 patients underwent ABO‐mismatched transplantation and the control group consisted of 252 patients with ABO‐matched allo‐PBSCT. We found a significant association between major‐0 ABO mismatch (group 0 recipient/group A, B, or AB donor) and increased red blood cell (RBC) and platelet transfusion requirements (both P <.001) as well as delayed platelet engraftment ( P <.001). Minor‐A (group A recipient/group 0 donor) and minor‐AB (group AB recipient/group 0, A, or B donor) ABO mismatch was significantly associated with an increased TRM after allo‐PBSCT ( P =.001 and P =.02). In multivariate analysis performed using Cox regression, minor ABO mismatch appeared as independent risk factor for TRM after allo‐PBSCT. No association was found for ABO mismatch with the incidence of GvHD, relapse, and OS. Our results suggest that ABO blood group mismatch has a significant impact on the outcome and that minor‐A and minor‐AB ABO mismatch represents a risk factor for increased TRM after allo‐PBSCT.